2022
DOI: 10.3390/ijerph19031605
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 6-Week Combined Balance and Plyometric Training on Dynamic Balance and Quickness Performance of Elite Badminton Players

Abstract: The study aimed to investigate the effect of combined balance and plyometric training on dynamic balance and quickness performance of elite badminton athletes. Sixteen elite male badminton players volunteered to participate and were randomly assigned to a balance-plyometric group (PB: n = 8) and plyometric group (PT: n = 8). The PB group performed balance combined with plyometric training three times a week over 6 weeks (40 min of plyometrics and 20 min of balance training); while the PT group undertook only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…Alikhani et al, observed that 6-week of PT improved dynamic balance and knee proprioception in female badminton players ( Alikhani et al, 2019 ). Additionally, Nepocatych et al (2018) observed that balance training can increase ankle stability by augmenting neuromuscular function and proprioception as well as the dynamic balance by optimizing the postural control system to more efficiently utilize multiple kinds of sensory inputs (e.g., visual, proprioceptive) ( Söderman et al, 2000 ; Guo et al, 2021 ; Lu et al, 2022 ). However, no significant difference in COP outcomes between CT and PT is observed here, though a greater percentage change in these outcomes was induced by CT compared to PT, which thus needs to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alikhani et al, observed that 6-week of PT improved dynamic balance and knee proprioception in female badminton players ( Alikhani et al, 2019 ). Additionally, Nepocatych et al (2018) observed that balance training can increase ankle stability by augmenting neuromuscular function and proprioception as well as the dynamic balance by optimizing the postural control system to more efficiently utilize multiple kinds of sensory inputs (e.g., visual, proprioceptive) ( Söderman et al, 2000 ; Guo et al, 2021 ; Lu et al, 2022 ). However, no significant difference in COP outcomes between CT and PT is observed here, though a greater percentage change in these outcomes was induced by CT compared to PT, which thus needs to be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Wedderkopp et al (2003) for example, showed that combined training of balance and strength is of great promise to reduce the incidence of injuries in young female handball players. Additionally, several of our previous studies showed that combined training of balance and PT significantly improved the capacity to adjust the direction of movements and dynamic balance, which are essential for athletic performance and the prevention of injury risk ( Guo et al, 2021 ; Lu et al, 2022 ). These findings suggest that compared to PT only, CT may induce greater benefits for athletes of badminton by simultaneously augmenting their knee function and proprioception, which, however, have not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance has evolved into a necessary physical component for badminton (Ilham et al, 2021). To become a national level badminton player, the average VO 2 max required is a minimum of 55 ml/minute/body weight for male athletes and 50 ml/minute/body weight for female athletes, but the field says otherwise (Lu et al, 2022). This was clearly seen when researchers observed badminton athletes based on the needs analysis with the test of badminton athletes aged 17-18 years still not entering the criteria, namely the acquisition of a VO 2 max value of 40.80-47.80ml/minute/ body weight for male badminton athletes (Saifu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(Zhannisa et al, 2018). Pada atlet bulutangkis keseimbangan termasuk ke dalam peranan penting mengatasi masalah mengontrol gerak gravitasi dan situasi lain yang berpengaruh pada keseimbangan, seperti gerakan memutar ketika menerima shuttlecock yang berada dibelakang badan, gerakan ketika mendarat setelah melakukan lompatan smash dan pada saat menerima serangan (Lu et al, 2022). Melakukan pelatihan keseimbangan dapat meningkatkan gerakan peforma pada atlet bulutangkis, khususnya performa dalam merubah arah gerak badan (Guo et al, 2021) Hasil uji homogenitas tes strok stand menggunakan teknik Levene Statistic didapatkan data bahwa menghasilkan homogen.…”
unclassified